2017
DOI: 10.1002/app.45723
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun carbon nanofiber web electrode: Supercapacitor behavior in various electrolytes

Abstract: Carbon nanofibers (CNFs) draw great interest due to their noticeable mechanical, electrochemical, and physical properties. In this study, polyacrylonitrile-based CNFs are obtained via electrospinning technique. Thermal oxidation and low temperature (950 8C) carbonization are applied to the electrospun web in order to achieve CNF. Through the process, Fourier transform infraredattenuated total reflectance spectroscopy and Raman spectroscopic results are investigated. The electrochemical properties of the self-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…Supercapacitors stand out with their superior characteristics such as high energy and power density, quick charge/discharge, wide working temperature ranges, and long cycle life 2‐4 . Although supercapacitors still find use in vehicles such as hybrid energy systems, and digital telecommunication systems, they can also be used in wearable electronics applications, as they can be made from flexible and lightweight materials 5‐10 …”
Section: Introductionmentioning
confidence: 99%
“…Supercapacitors stand out with their superior characteristics such as high energy and power density, quick charge/discharge, wide working temperature ranges, and long cycle life 2‐4 . Although supercapacitors still find use in vehicles such as hybrid energy systems, and digital telecommunication systems, they can also be used in wearable electronics applications, as they can be made from flexible and lightweight materials 5‐10 …”
Section: Introductionmentioning
confidence: 99%
“…Ismar et al . have also fabricated PAN‐derived CNF webs as supercapacitor electrode materials via electrospinning, thermal oxidation, and low temperature carbonization . They found that specific capacitance values of the PAN‐derived CNF webs are in the range of 149‐204 F/g, depending on the electrolyte type.…”
Section: Introductionmentioning
confidence: 94%
“…7 Carbon materials are widely used for supercapacitor electrode materials due to their low cost, high performance, and versatile existing forms such as powders, fibers, felts, and composites. [8][9][10][11][12][13] Especially, carbon nanofibers (CNFs) have high electrical conductivity, specific surface area, mechanical stability, and electrolyte wettability. 14 CNFs can be fabricated simply and efficiently by carbonizing electrospun polymeric nanofibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Capacitor component was parallel to the constant phase element (Q) and Rct units. CPE was applied to the circuit model together with the n, which is the correction factor due to porous and inhomogeneity of the structure; if n is equal to 1, it shows the ideal capacitor . Figure A represents the equivalent circuit modelling of EIS data with components Rs, Rct, C, and Q, while Table gives the fitting parameters of impedance data according to EIS measurements.…”
Section: Electrochemical Impedance Spectroscopy (Eis) and Equivalent mentioning
confidence: 99%